Road map for revolutionaries : resistance, activism, and advocacy for all - Camahort Page, Elisa; Gerin, Carolyn; Wilson, Jamia, 1980- (Ten Speed Press, 2018)
"A simple-to-follow, boots-on-the-ground, open-anywhere guidebook that delivers practical tactics for navigating, affecting, and protecting your own personal democracy in a gridlocked, heavily surveilled, and politically volatile United States. With infographics, links to resources and communities, and words of wisdom from people already fighting the good fight, this guidebook is meant to be used and abused. It's designed to move you from idea to action to part-time revolution in a quick, efficient, and effective manner"--